PENINGKATAN KEMAMPUAN MENGENAL HURUF MELALUI MEDIA TUTUP BOTOL HURUF ANAK USIA 5-6 TAHUN DI TK ISLAM TERPADU ROBBANI INDRALAYA - Serli Oktarini; Yuni Dwi Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the concentration ability of children aged 5–6 years through actively and engagingly designed learning activities at TK Islam Terpadu Robbani Indralaya. Based on the initial observations, the children’s letter-recognition skills were still relatively low at 50%, as indicated by their lack of focus during learning activities, resulting in their inability to meet the Early Childhood Development Achievement Standards (STTPA).This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action implementation, observation, and reflection. The research subjects were 10 children aged 5–6 years. Data were collected through observation, interviews, and documentation, while data analysis was carried out descriptively. The results of the study show an improvement in children’s concentration ability in each cycle. The average level of mastery of concentration skills during the pre-action stage was 43.44%, increasing to 63.50% in Cycle I, and showing a more significant increase in Cycle II with an average of 80.66%. This improvement indicates that the implemented actions successfully helped the children enhance their focus and attention throughout the learning process.